(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The possibility of mass trapping or mating disruption of Ephestia kuehniella (Zell.) in a department of an industrial bakery heavily infested has been evaluated. The trials lasted 20 months, using ever increasing quantities of TDA and laminar dispensers located on the walls and on machinery. It was noted that in these conditions even the use of high doses of TDA can reduce, but not block completely the reproduction of Ephestia kuehniella. As far as mass trapping is concerned more than 16.000 adults have been captured on the whole, but it was not possible to lower the population to acceptable levels. The use of high doses of TDA does not interfere completely with the reproduction of the insect, which is little active and often nests in pipes and machinery. Only using a dosage of 50 mg of TDA per erogator, with a concentration of 1.5 mg/m3 of environment, it was possible to inhibit mating. In order to be successfull with these techniques, it is necessary to clean accurately, to remove the debris from the most neglected corners, reducing the possibilities of nesting of this insect.